Invasive Species of Florida’s Coastal Waters: The Red Lionfish (Pterois volitans) and Devil Firefish (P. miles) - Maia McGuire; Jeffrey Hill (EDIS, 2013)
Two species of Indo-Pacific lionfish (Pterois volitans and P. miles) are the first reported non-native marine fish to become established in the Atlantic Ocean. Genetic studies indicate that lionfish in the Atlantic are likely all descendants of a few individuals, consistent with the widely held belief that lionfish were introduced into the Atlantic as a result of accidental or deliberate release of aquarium pets. Regardless of the method of introduction, the prolific spread of these invasive species in the Atlantic Ocean ecosystem is cause for concern. This 5-page fact sheet was written by Maia McGuire and Jeffrey Hill, and published by the UF Department of Sea Grant, January 2014. http://edis.ifas.ufl.edu/sg132